2012
DOI: 10.3109/2000656x.2012.700005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of modified Kessler and Yotsumoto-Dona suture: A biomechanical study on porcine tendons

Abstract: There is a need for a strong suture technique that allows early active mobilisation after repair of flexor tendons, but the best method has not yet been found. The aim of this study was to compare the modified Kessler suture biomechanically with a newer, two-strand suture. Eighteen porcine tendons were cut and repaired according to either the grasping modified Kessler suture or the combined side-locking loop technique (Yotsumoto) and interlocking horizontal mattress suture (Dona). The specimens were tested lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 95 publications
(203 reference statements)
0
9
0
Order By: Relevance
“…A total of 287 FDP tendons were repaired with a traditional 2-strand modified Kessler technique completed with a simple running suture. A side-locking loop repair (Yotsumoto et al, 2005) combined with interlocking horizontal mattress epitendinous suture (Dona et al, 2003; Rigó et al, 2012) was performed on 61 FDP tendons, and a double Kessler (Smith and Evans 2001) repair in eight. The material of the core suture was braided polyblend polyethylene (FiberWire; Arthrex Co., Naples, FL, USA) in the Yotsumoto-Dona repair; otherwise monofilament polypropylene (Prolene; Ethicon, Sommerville, NJ, USA) in 107, monofilament nylon (Dermalon; Covidien Ltd., Mansfield, MA, USA) in 78, and polydioxanole (PDS; Ethicon, Somerville, NJ, USA) in 10 FDP repairs.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 287 FDP tendons were repaired with a traditional 2-strand modified Kessler technique completed with a simple running suture. A side-locking loop repair (Yotsumoto et al, 2005) combined with interlocking horizontal mattress epitendinous suture (Dona et al, 2003; Rigó et al, 2012) was performed on 61 FDP tendons, and a double Kessler (Smith and Evans 2001) repair in eight. The material of the core suture was braided polyblend polyethylene (FiberWire; Arthrex Co., Naples, FL, USA) in the Yotsumoto-Dona repair; otherwise monofilament polypropylene (Prolene; Ethicon, Sommerville, NJ, USA) in 107, monofilament nylon (Dermalon; Covidien Ltd., Mansfield, MA, USA) in 78, and polydioxanole (PDS; Ethicon, Somerville, NJ, USA) in 10 FDP repairs.…”
Section: Methodsmentioning
confidence: 99%
“…The repair was completed with a running epitendinous suture with 5-0 monofilament nylon (Dermalon; Covidien Ltd, Mansfield, MA, USA) in an interlocking horizontal mattress suture fashion (Figure 1) (Dona et al., 2003). This repair configuration is similar to the Silfverskõild repair (Silfverskiöld and May, 1994), with the differences in use of FiberWire as the suture material and locking loops of the core suture placed on the side instead of the volar surface of the tendon and in use of Dona’s interlocking horizontal mattress suture instead of cross-stitches in making peripheral sutures (Rigó et al, 2012). In cases with avulsion or a distal tendon stump too short for placement of a suture, the tendon was reattached with transverse intraosseous loop technique (Figure 1) (Rigo and Røkkum, 2013; Tripathi et al., 2009).…”
Section: Methodsmentioning
confidence: 99%
“…99 In the past, the canine model was relied upon to perform research on flexor tendons. 98-100 More recently, a wider variety of animals have been used to characterise flexor tendon injury and repair, including chicken, 101 canine, 102-104 ovine, 105 porcine, 106,107 and rabbit 105-110 models. The best choice of model system will depend on the essential characteristics that must be mimicked for a particular research question.…”
Section: Flexormentioning
confidence: 99%
“…Recently, an ex vivo uniaxial test demonstrated that the Yotsumoto-Dona technique, a side-locking loop structure paired with a horizontal mattress peripheral suture, performed significantly better in 2 mm gap force, yield force, ultimate force, stiffness, energy to yield, and energy to failure tests when compared with the often-used modified Kessler technique, which consists of a grasping type structure, paired with a running peripheral suture. 106 In a separate ex vivo study, pulley-wrapped tension was applied to the tendon to better simulate gliding over bony surfaces. 107 In this case, the interrupted horizontal mattress technique proved to be significantly more effective in regards to ultimate tensile strength and resistance to gapping.…”
Section: Flexormentioning
confidence: 99%